2020
DOI: 10.22158/jecs.v4n3p130
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Access to Academic Accommodations Varies as a Function of School Type, Selectivity, and Cost

Abstract: Students with disabilities face many challenges in their pursuit of higher education. Academic accommodations and other educational supports can allow these students to learn, and to demonstrate their learning, in a manner similar to their classmates without disabilities. The purpose of this study was (1) to determine the percent of students classified with disabilities and receiving accommodations in college and (2) to see if students’ access to accommodations varies as a function of their college’s type, sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…General student populations perform better academically in environments that offer additional flexibility and choice (Bennett et al, 2006), including presenting information in more than one way (text, images, video, etc.) to support different learning styles (Babbitt & Miller, 1996; Dimitriadi, 2001) and when adequate supports and coping strategies are available for students (Cohen et al, 2020; Gersten & Baker, 2001; Karabenick, 2004; Malmivuori, 2006; Mercier & Frederiksen, 2007). We provide specific suggestions for incorporating a neurodiversity-informed UDL approach to academic settings, and note that most strategies can be incorporated at no or low cost.…”
Section: Utilizing the Domains Of Inclusion To Increase Accessmentioning
confidence: 99%
“…General student populations perform better academically in environments that offer additional flexibility and choice (Bennett et al, 2006), including presenting information in more than one way (text, images, video, etc.) to support different learning styles (Babbitt & Miller, 1996; Dimitriadi, 2001) and when adequate supports and coping strategies are available for students (Cohen et al, 2020; Gersten & Baker, 2001; Karabenick, 2004; Malmivuori, 2006; Mercier & Frederiksen, 2007). We provide specific suggestions for incorporating a neurodiversity-informed UDL approach to academic settings, and note that most strategies can be incorporated at no or low cost.…”
Section: Utilizing the Domains Of Inclusion To Increase Accessmentioning
confidence: 99%
“…Although it has been suggested that Universal Design for Learning can be used to minimize academic accommodations (Gidden & Jones, 2021), there is little data to suggest that this is actually feasible in many institutions. Moreover, data show that fewer than 50% of students with disabilities register to receive accommodations both in Canada (Fichten et al, 2018;2019a) and America (Cohen et al, 2020;McGregor et al, 2016;Newman et al, 2016;Parsons et al, 2021). There are a variety of barriers to registering, as reviewed by Toutain (2019).…”
Section: Nature Of Accommodationsmentioning
confidence: 99%
“…It is also noteworthy that data show that fewer than half of the students who self-report a disability are registered to receive accommodations (Cohen et al, 2020;Fichten et al, 2018;2019b;McGregor et al, 2016;Newman et al, 2016;Parsons et al, 2021). Considering this statistic and factoring in our findings of self-reported multiple disabilities, it begs the question of whether the need for documentation presents a barrier to eligibility and should be reconsidered for government regulations regarding funding and for institutional guidelines to allow for greater access to accommodations for students with a history of academic challenges.…”
Section: Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Students with the social awareness to know that accommodations are available; the support of parents, teachers, and other individuals to seek them out; and the cultural, linguistic, and self-advocacy skills to convince disability professionals that they are warranted may be most likely to receive services, regardless of their disability status (Waterfield and Whelan, 2017). In contrast, reliance on interviews, impressions, and instincts may disadvantage students with disabilities who lack these resources (Bolt et al, 2011;McGregor et al, 2016;Lovett, 2020;Cohen et al, 2021). Indeed, the number of students receiving accommodations has increased exponentially at America's most selective and expensive private colleges, whereas access to accommodations at community colleges has remained low (Weis and Bittner, 2022).…”
Section: Introductionmentioning
confidence: 99%